2013
DOI: 10.1165/rcmb.2012-0059ps
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Fibrosis Therapy: A Community Ecology Perspective

Abstract: and 7 Rainbow Rock, Ocean View, Hawaii Current therapy for cystic fibrosis (CF) focuses on minimizing the microbial community and the host's immune response through the aggressive use of airway clearance techniques, broad-spectrum antibiotics, and treatments that break down the pervasive endobronchial biofilm. Antibiotic selection is typically based on the susceptibility of individual microbial strains to specific antibiotics in vitro. Often this approach cannot accurately predict medical outcomes because of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
123
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(135 citation statements)
references
References 59 publications
10
123
0
2
Order By: Relevance
“…WinCF and the climax and attack model (CAM) The CAM proposed that there are two functionally different microbial communities in the CF lungs (Conrad et al, 2012). Growth of the Attack Community, consisting of transient viral and microbial populations, is predicted to induce strong immune responses, which create microenvironments that facilitate establishment of a Climax community that is slower growing and inherently resistant to antibiotic therapy (Conrad et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…WinCF and the climax and attack model (CAM) The CAM proposed that there are two functionally different microbial communities in the CF lungs (Conrad et al, 2012). Growth of the Attack Community, consisting of transient viral and microbial populations, is predicted to induce strong immune responses, which create microenvironments that facilitate establishment of a Climax community that is slower growing and inherently resistant to antibiotic therapy (Conrad et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Growth of the Attack Community, consisting of transient viral and microbial populations, is predicted to induce strong immune responses, which create microenvironments that facilitate establishment of a Climax community that is slower growing and inherently resistant to antibiotic therapy (Conrad et al, 2012). Metagenomics studies have shown that the core physiology of the CF microbial community contains both respiratory and fermentative pathways for energy generation .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter is tempered by the idiosyncratic nature of information gathering and translation into a rational treatment. Related perspectives have recently been discussed for parasites [6], pathogenic bacteria (e.g., [7]), and cancer [8,9]. Figure 1 shows an oversimplified depiction of one type of disease ecosystem: the cancer microenvironment.…”
Section: The Disease Ecosystemmentioning
confidence: 99%